Comparing comparisons: Assimilation and contrast processes and outcomes following social and temporal comparison. Issue 6 (17th August 2020) - Vogel, Erin A.; Rose, Jason P.; Aspiras, Olivia G.; Edmonds, Keith A.; Gallinari, Elizabeth F.
ABSTRACT: The present research examines similarities and differences between social and temporal comparison processes in a health-related context. In two studies, participants were randomly assigned to write about an upward or downward, social or temporal comparison target. Participants then reported their perceived similarity to the target and evaluated their own fitness. Consistent with hypotheses, participants who perceived themselves as similar (dissimilar) to an upward comparison target had more positive (negative) self-evaluations. These outcomes reflect assimilation and contrast processes, respectively, though effects were attenuated among those who made downward temporal comparisons in Study 1 and upward comparisons in Study 2. Results suggest that upward social and temporal comparison processes, once engaged, produce similar assimilative and contrastive outcomes.